Etching of 316L Stainless Steel by Different Chemical Etchant Solutions for the Growth of Carbon Nanotubes by Thermal Chemical Vapour Deposition - Cheraghali, R.; Moradi, Sh.; Ghoranneviss, M.; Aberom Azar, P.; Khorrami, S.A. (Asian Journal of Chemistry, 2011)
We report and interpret the effectiveness of different etching with different and well-known etching chemical reagents such as Kallings number 1, Kallings number 2, Kellers, kroll, nital, marble, picral reagents on stainless steel as a substrate to synthesize carbon nanotubes. Suitable pretreatment of stainless steel substrates was required for the satisfactory growth of carbon nanotubes on them. Carbon nanotubes were grown on stainless steel by thermal chemical vapour deposition, using acetylene as hydrocarbonic gas and hydrogen as diluted one in atmospheric pressure at 800 ºC. It was found that the density of carbon nanotubes decreases as the roughness on the surface is reduced.